A modelling approach to classify the suitability of shallow Mediterranean lagoons for pacific oyster, Crassostrea gigas (Thunberg, 1793) farming. (1st July 2020) - Graham, Philip; Falconer, Lynne; Telfer, Trevor; Mossone, Paolo; Viale, Iolanda; Carboni, Stefano
Abstract: In this study, we have developed an approach to classify the suitability of shallow coastal lagoons for pacific oyster aquaculture as the first step in a site selection process. Historical bio-physical data and local knowledge were combined to produce overall scores for biological and logistical criteria relevant for oyster farming which were then combined using Multi-Criteria Analysis (MCA) for an overall lagoon suitability score. A Dynamic Energy Budget growth model was also used to identify and rank suitability of shallow coastal lagoons to host Pacific oysters farming sites. Furthermore, modelled growth data were used to estimate the production cycle length and the potential productivity of the newly identified sites. The results indicated that biological and logistic factors were suitable for Pacific oyster farming in eleven out of twelve of the lagoons considered. However, acquiring water classification for shellfish farming and maintaining high water quality standards will be critical for any sustainable development of culture areas. Potential production figures and logistic scores, clearly indicates in which lagoons investments should be focused and what output could be realised from these very productive ecosystems. The results can be used to indicate where more detailed assessment should take place. As remote-sensing technologies continue to develop and algorithms for the interpretation of ocean colour in coastal areas keep improving, this multidisciplinary approach will increase our ability to estimate aquaculture production in complex aquatic systems. This approach will provide stakeholders, policy makers and regulators with a new and powerful decision-making tool for site selection of sustainable oyster farming activities and the management of the surrounding coastal areas. Graphical abstract: Image 1 Highlights: Classification of coastal lagoons suitability for Pacific oyster farming site selection. Multidisciplinary approach combining biological, logistical and geographical data. Prioritisation of investments for sustainable coastal zone management.